HUBUNGAN PREEKLAMSIA DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH - Oktarina, Mika; Herdiani, Tria Nopi; Rahmawati, Ida; Susanti, Ratna (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Preeclampsia and eclampsia is a complication in the labor process whose incidence is always high. The purpose of this study was to study the relationship between Birth Weight and the incidence of preeclampsia in RSUD dr. M. Yunus, Bengkulu city in 2017. The type of research used in this study is Survey Analytic using the Cross Sectional method. The population in this study was overall in the hospital of Dr. M. Yunus City of Bengkulu in January to December in 2017 which is 362 babies. The sampling technique in this study was 78 proportional sampling. The data used is secondary data obtained from the patient register at Dr. M Yunus Hospital in Bengkulu. Data were analyzed using univariate and bivariate analysis with Chi-Square test (ï£2) and Contingency Coefficient (C) test. The results obtained: Of the 78 newborns sampled there were 60 infants (76.9%) normal birth weight, 55 people (70.5%) did not experience preeclampsia, there was a significant relationship between preeclampsia and low infant weight in RSUD dr. M. Yunus Bengkulu in the tight category. It is expected that health workers can maintain and improve the quality of their abilities and skills to deal with babies with low birth weight born by preeclampsia patients or other patients.